Dynorphin and [kappa]-Opioid receptor dysregulation in the dopaminergic reward system of human alcoholics - Bazov, Igor; Hansson, Anita C.; Sommer, Wolfgang H.; Spanagel, Rainer (Molecular neurobiology, 2018)
Molecular changes induced by excessive alcohol consumption may underlie formation of dysphoric state during acute and protracted alcohol withdrawal which leads to craving and relapse. A main molecular addiction hypothesis is that the upregulation of the dynorphin (DYN)/κ-opioid receptor (KOR) system in the nucleus accumbens (NAc) of alcohol-dependent individuals causes the imbalance in activity of D1- and D2 dopamine receptor (DR) expressing neural circuits that results in dysphoria. We here analyzed post-mortem NAc samples of human alcoholics to assess changes in prodynorphin (PDYN) and KOR (OPRK1) gene expression and co-expression (transcriptionally coordinated) patterns. To address alterations in D1- and D2-receptor circuits, we studied the regulatory interactions between these pathways and the DYN/KOR system. No significant differences in PDYN and OPRK1 gene expression levels between alcoholics and controls were evident. However, PDYN and OPRK1 showed transcriptionally coordinated pattern that was significantly different between alcoholics and controls. A downregulation of DRD1 but not DRD2 expression was seen in alcoholics. Expression of DRD1 and DRD2 strongly correlated with that of PDYN and OPRK1 suggesting high levels of transcriptional coordination between these gene clusters. The differences in expression and co-expression patterns were not due to the decline in neuronal proportion in alcoholic brain and thereby represent transcriptional phenomena. Dysregulation of DYN/KOR system and dopamine signaling through both alterations in co-expression patterns of opioid genes and decreased DRD1 gene expression may contribute to imbalance in the activity of D1- and D2-containing pathways which may lead to the negative affective state in human alcoholics.